Pore Size Distribution and Pore Connectivity Response Characteristics of Anthracite Injected with Carbon Dioxide in Different Phases - Yi, Jiale (International Journal of Natural Resources and Environmental Studies, 2024)
The adsorption of CO2 changes the pore content in coal. After CO2 adsorption, pore content in coal shows a trend of first increasing, then decreasing and then increasing. CO2 adsorption pressure, CO2 adsorption time and CO2-H2O slightly change the variation range of pore size, but the trend remains unchanged. For example, in the case of CO2 adsorption for 72 hours, the pore content of 2 10nm and >700nm is generally increased, and the pore content of 10 700nm is significantly reduced. In the case of 144 hours of CO2 adsorption, the pore content of 2 20nm and >700nm generally increased, and the pore content of 20 700nm significantly decreased. When water +CO2 was adsorbed for 144 hours, the pore content of 2 12nm and >700nm generally increased, and the pore content of 12 700nm generally decreased. The coal samples show a certain lag of mercury removal before and after CO2, which indicates that there are some ineffective pores in the coal. The mercury removal efficiency of the coal sample after CO2 adsorption is generally lower than that of the dry sample, indicating that a large number of inefficiently connected pores are generated after CO2 adsorption. That is, CO2 does increase a large number of pores in coal, but the pores are mainly non-connected pores, that is, CO2 has a weak improvement in the connectivity of the pores in coal